Fostering knowledge sharing and knowledge utilization: The impact of organizational commitment and trust. Issue 4 (3rd July 2019) - Ouakouak, Mohammed Laid; Ouedraogo, Noufou
Abstract : Purpose: The purpose of this paper is to explore the influence of organizational commitment and trust on knowledge sharing and on knowledge utilization. Also, the study aims to examine the influence of knowledge sharing on knowledge utilization. Design/methodology/approach: A quantitative study was conducted among 307 employees working at Canadian organizations. Findings: The results reveal that both affective commitment and professional trust have positive influences on knowledge sharing and knowledge utilization, whereas personal trust and continuance commitment do not. The authors also found that business ethics moderates the relationship between knowledge sharing and knowledge utilization. Practical implications: These findings extend the literature on knowledge management and demonstrate, from a practical perspective, that in order to build a knowledge-sharing culture, managers must create conditions that allow affective commitment, professional trust and business ethics to flourish. Originality/value: The current study offers an initial investigation of the effects of both kinds of commitment and trust on knowledge sharing and knowledge utilization.